2002
DOI: 10.1063/1.1430440
|View full text |Cite
|
Sign up to set email alerts
|

Self-similarity theory of stationary coagulation

Abstract: A theory of stationary particle size distributions in coagulating systems with particle injection at small sizes is constructed. The size distributions have the form of power laws. Under rather general assumptions, the exponent in the power law is shown to depend only on the degree of homogeneity of the coagulation kernel. The results obtained depend on detailed and quite sensitive estimates of various integral quantities governing the overall kinetics. The theory provides a unifying framework for a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The grain number density distribution in the case of such a fragmentation cascade has been derived by Dohnanyi (1969) and Williams & Wetherill (1994) and was found to follow a power-law number density distribution n(m) ∝ m −α with index α = 11 6 (which is equivalent to n(a) ∝ a −3.5 ), with very weak dependence on the mechanical parameters of the fragmentation process. Tanaka et al (1996), Makino et al (1998) and Kobayashi & Tanaka (2010) showed that this result is exactly independent of the adopted collision model and that the resulting slope α is only determined by the mass-dependence of the collisional cross-section if the model of collisional outcome is self-similar (in the context of fluid dynamics, the same result was independently obtained by Hunt 1982 andPushkin &Aref 2002). The value of 11 6 agrees well with the size distributions of asteroids (see Dohnanyi 1969) and of grains in the interstellar medium (MRN distribution, see Mathis et al 1977;Pollack et al 1985) and is thus widely applied, even at the gas-rich stage of circumstellar disks.…”
Section: Introductionmentioning
confidence: 52%
“…The grain number density distribution in the case of such a fragmentation cascade has been derived by Dohnanyi (1969) and Williams & Wetherill (1994) and was found to follow a power-law number density distribution n(m) ∝ m −α with index α = 11 6 (which is equivalent to n(a) ∝ a −3.5 ), with very weak dependence on the mechanical parameters of the fragmentation process. Tanaka et al (1996), Makino et al (1998) and Kobayashi & Tanaka (2010) showed that this result is exactly independent of the adopted collision model and that the resulting slope α is only determined by the mass-dependence of the collisional cross-section if the model of collisional outcome is self-similar (in the context of fluid dynamics, the same result was independently obtained by Hunt 1982 andPushkin &Aref 2002). The value of 11 6 agrees well with the size distributions of asteroids (see Dohnanyi 1969) and of grains in the interstellar medium (MRN distribution, see Mathis et al 1977;Pollack et al 1985) and is thus widely applied, even at the gas-rich stage of circumstellar disks.…”
Section: Introductionmentioning
confidence: 52%
“…the formation of a particle of infinite mass at finite time [12,13,14]. Similarities between the SCE and turbulence theory have been discussed previously [15], with an explicit discussion of locality of interactions. In this paper, we use results from an interacting particle system to highlight the importance of this assumption of locality when deriving scaling solutions.…”
Section: Introductionmentioning
confidence: 58%
“…By applying a dimensional analysis, Hunt (1982) showed the steady state floc size distribution follows a power law. Pushkin and Aref (2002) later developed a more rigorous self-similarity theory of stationary coagulation and showed the floc size distribution follows a power law in the coagulating system. In these studies, the system is forced with particle injection at small sizes, and breakup is not considered.…”
Section: Introductionmentioning
confidence: 99%